A Typo-Structural Exploration of the Monumental Portals of Sinan’s 16th-Century Ottoman Mosques in Istanbul - Elagöz Timur, Bahar; Timur, Bahar Elagoz (Springer Science and Business Media B.V., 2026)
Ottoman architectural portals are significant as grand entrances to mosque complexes, symbolizing the transition from the secular to the sacred. Their design reflects the artistic sophistication of the Ottoman Empire, blending functionality with aesthetic appeal. This article highlights significant aspects of monumental portal construction, showcasing a blend of form, materials, and engineering that exemplifies architectural progress. These portals are monumental entrances to mosque complexes, embodying the structural integrity and aesthetic of Ottoman architecture. Key features include load-bearing systems that distribute weight and provide stability, combining arches and columns to create large openings without sacrificing strength. These elements enhance the portals' visual grandeur and durability time. A study was conducted on the monumental portals of 16th-century mosques designed by Architect Sinan, widely regarded as the most famous Turkish architect. Within the scope of this study, the structural analysis of these masonry portals of five mosques - Sehzade Mehmed, Uskudar Mihrimah Sultan, Rustem Pasha, Edirnekapi Mihrimah Sultan, and Kilic Ali Pasha mosques- will be carried out. It examines the material properties, the arrangement of structural elements, and the relationship between the portals and the main structures according to the load-carrying principles. The analysis is supported by typological studies and 3d models, allowing for a comprehensive comparison across the selected examples. These, commissioned by prominent political figures and built by Turkey's greatest architect, are significant historical architectural components that establish a connection with the public. Therefore, these structural analyses and documentation are proposed to contribute to their conservation.
Keywords: Architect Sinan; Masonry; Monumental Portals; Decoding Structures; Ottoman Architecture; Cultural Heritage